Can SHED or DPSCs be used to repair/regenerate non-dental tissues? A systematic review of in vivo studies - Felipe Perozzo DALTOÉ; Priscila Pedra MENDONÇA; Andrea MANTESSO; Maria Cristina Zindel DEBONI (Sociedade Brasileira de Pesquisa Odontológica, 2014)
Dental pulp has been identified as a novel and promising stem cell source. The following systematic review presents and summarises in vivo studies that have used stem cells from the dental pulp of permanent and deciduous teeth to repair or regenerate non-dental tissues. An electronic customised search was performed using 4 different databases (Entrez PubMed, Cab Abstracts, Scopus and Web of Science). Only full-text research manuscripts published in English between the years of 2000 and 2012 were included. The manuscripts were retrieved based on the following keywords and/or abbreviations: [Stem Cells from Human Exfoliated Deciduous teeth (SHED)] AND/OR [Dental Pulp Stem Cells (DPSC)] AND [tissue regeneration] AND [tissue repair]. Only manuscripts involving in vivo applications of SHED or DPSC for the repair and/or regeneration of non-dental tissues were included. The search strategy produced 2309 papers, from which 14 were eligible according to the predetermined inclusion and exclusion criteria. Although human tissue was the source of cells in half of the studies included in our review, all of the studies involved transplantation into animals of other species, such as pigs, rats and mice. Most of the manuscripts reported the successful use of DPSCs or SHED for non-dental tissue repair or regeneration. While these cell populations represent promising alternative sources of stem cells for tissue engineering and cell-based regenerative medicine therapies, it is not yet possible to guarantee the appropriate clinical management of this technique.